PENGARUH LATIHAN COPING WITH STRESS TERHADAP RISIKO BUNUH DIRI PADA REMAJA DI SMP KASIH KOTA DEPOK TAHUN 2010 - Tinneke A. Tololiu; Budi Anna Keliat; Etty Rekawati (Jurnal Ilmiah Perawat Manado (Juiperdo), 2012)
Coping with stress exercise program is one form of mental health services, community-based youthheld at the school. The purpose of this study is to get a view of the influence of coping with stressexercise program against the risk of suicide among adolescents in junior high school love of Depok.Design research is a "Quasi-experimental pre-post test with control group." The sample is a clustersampling technique with a sample size of 56 junior high school adolescent students. This programaims to train youth to have self-defense capability so that when the stress remains at a low levelwithout destructive behavior. Risk of suicide in adolescents measured by using AdolesenceDepression Rating Scale (ADRS) and then analyzed using statistics. The results showed a reducedrisk of suicide significantly in the group of teenagers who were trained compared with those whowere not trained (p-value <0.05). Coping with stress exercise program in adolescents, it isrecommended to be done in order for mental health services in the community as a form of schoolbasedmental health services